Optimization of different builders in formulation of protease detergent using response surface methodology approach - Lishalan Periasamy (2024)
Proteases present in detergents efficiently break down protein residues from blood, grass, and egg, converting them into soluble peptides that can be easily washed away by the detergent. Optimize detergent formulations through Response Surface Methodology with varied enzyme and builder concentrations to enhance cleaning efficacy and efficiency. The objective of this study is to determine the most effective detergent builders based on the washing performance evaluations and to optimize and select the optimal detergent formulation with the chosen builders through washing performance assessments using Response Surface Methodology. The study assessed detergent effectiveness on cotton fabric stained with chicken blood, grass, and egg yolk. Seven formulations were tested, including controls with and without EDTA, and distilled water. Five formulations with varied builders (sodium tetraborate, sodium carbonate, sodium citrate, sodium silicate, and citric acid) were evaluated. The most efficient builder was selected, and its concentration, along with enzyme, was optimized using Response Surface Methodology. Stain removal was measured using the CIELAB system. This study showed that citric acid and sodium silicate were the most effective builders among all the six builders. From the response surface methodology analysis revealed that enzyme concentration consistently influenced stain removal, with sodium silicate and citric acid effects varying by stain type. In conclusion, our study highlights the significant role of builders in improving stain removal, recommending further optimization of detergent formulations for enhanced performance.